KOMPOSISI KIMIA DAN STABILITAS PUREE BUAH MERAH (Pandanus conoideus Lamk.) SELAMA PENYIMPANAN - Dela Vikantika Ponglabba; Zita Letviany Sarungallo; Budi Santoso (JURNAL AGROTEKNOLOGI, 2022)
Red fruit (Pandanus conoideus Lamk.) is an endemic plant of Papua containing active components (carotenoids and tocopherols) as antioxidants and potential as a functional food. Until now, red fruit is only used for produce oil, while the information on the flesh of the fruit for raw materials of various food products is still limited, such as the chemical content, active components, and stability. The objectives of this study were to determine the nutritional composition and active components of red fruit puree and evaluate the stability of red fruit puree during storage. The puree of the red fruit was packed in a glass bottle and stored at room temperature (30±2°C) for 60 days to tested their quality stabilities. Parameters of color, aroma, taste, emulsion stability, viscosity, total dissolved solids, and acidity were observed on days 0, 10, 20, 30, 40, and 60 during storage. While total carotenoids were observed on days 0, 20, 40, and 60. The results showed that the nutritional content of red fruit puree in 100 g of dry weight included water content of 55.8%, ash content of 2.22%, fat content of 67.39%, protein content of 7.84%, and carbohydrate content of 22.56 %. Whereas, the active compounds, namely total carotenoids of 2003 ppm, β-carotenoids of 19 ppm, total tocopherol of 502 ppm, and -tocopherol of 371 ppm. During 60 days of storage, the color, aroma, taste, emulsion stability, total dissolved solids, and pH of red fruit puree were relatively stable. However, the viscosity was stable until day 40 and total carotenoids tended to decrease. This puree contains high carotenoids and tocopherols, so it has the potential as a functional food that is good for health. Keywords: carotenoid, emulsion, functional food, tocopherol